Implementasi Aplikasi Sistem Keuangan Desa (SISKEUDES) sebagai Upaya Peningkatan Akuntabilitas Keuangan Desa di Desa Tebel Kecamatan Gedangan Kabupaten Sidoarjo - Rahmawati, Maretta Ayu; Krisnawati, Anggi; Nadzah, Savinathul; Widianti, Nanda Putri; Utomo, Harun Ar-Rasyid (SUSTAINABLE, 2024)
This study analyzes the implementation of the Village Financial System Application (SISKEUDES) in Tebel Village, Gedangan District, Sidoarjo Regency, to improve village financial accountability. Good financial management is essential to achieve transparency. SISKEUDES, developed by BPKP, aims to assist villages in more effective and efficient financial management. The method used is qualitative with interviews with resource persons. The results show that the implementation of SISKEUDES in Tebel Village contributes positively to accountability and transparency, but this success is influenced by factors such as the adequacy of human resources, effective communication, and bureaucratic support. Challenges include a lack of understanding and training for village officials. Overall, SISKEUDES has proven to be effective in improving village financial governance. This research is expected to provide insights for the development of village financial policies in the future and become a reference for other villages in utilizing information technology to increase accountability and transparency. Keywords: Implementation, SISKEUDES, Village Finance, Accountability, Sidoarjo Regency